Conditions Associated with Childhood Asthma in North Texas. (24th September 2012) - Newcomb, Patricia; Cyr, Alaina
Abstract : Introduction . The purpose of this study was to identify significant associations between asthma diagnosis, comorbid conditions, and social problems in children. Method . This study explored data collected in a unique, regional survey of children's health in north Texas originally administered in 2009 to a random sample of 21, 530 households with children from 0 to 14 years of age. Descriptive statistics were compiled for the subsample of children with asthma, associations of interest were identified, and strengths of relevant associations were calculated. Results . The prevalence of asthma in school-aged children in the target area is 19–25%, which exceeds both national and state values. Statistically significant associations were found between asthma and allergies, sleep problems, and tonsillectomy. Significant associations were identified between asthma and school absences, academic problems, and behavior problems in school. There was a significantly greater prevalence of obesity/overweight among children with asthma than without asthma. Discussion . Children with asthma are at high risk for impairment in multiple dimensions. Thorough assessment, including comprehensive medical, social, and environmental histories, is critical in management of pediatric asthma.